Сurrent issues of development and introduction of electronic textbooks into vocational education system - Didenko, Oleksandr (Professional Pedagogics, 2014)
The article deals with relevance of development and introduction of e-textbooks into vocational education system, which is stipulated by current needs and requirements of legal documents regulating vocational education. To reveal the aforementioned points a generalization of results of modern scientific, educational and psychological literature analysis as regards requirements to development of e-textbooks and peculiarities of their introduction into vocational education system is presented. The results of publications analysis on the issues studied suggest that theoretical and empirical investigations cover a range of issues in this area. The essence of the concept «electronic textbook» as well as a theoretical basis for its design – theory of immediate memory capacity and features of central nervous system is defined. The author presents an established classification of e-textbooks and their requirements based on achievements of modern information technology. Strengths and weaknesses of e-learning are also characterized. Since the problem of providing training courses at vocational schools with textbooks of new generation is among the most important ones in the context of modern educational technologies introduction into teaching and manufacturing process, it is determined that they should be characterized not only by new principles of structuring and selection of content, but also take into account psychological features as to modern perception of educational material by young people. For this brief material concerning vocational schools pupils’ age and individual psychological characteristics that should be considered while developing e-textbooks is given. However, it is proved that in spite of all the benefits e-textbooks have, they should not be considered as a versatile new information and educational tool. Prospects for further research is to study experience of European countries with the best education system regarding development, implementation and use of electronic aids and textbooks.
Keywords: electronic textbook; vocational education; digital library; electronic document; vocational schools students